PENERAPAN CARING DAN SPIRITUAL PERAWAT PADA PASIEN KRITIS DI RUANG ICU - Betty; Husna, Elfira (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2019)
Nursing care focuses on caring. Nurse As a professional health professional, providing servicesmust be based on a holistic function, covering all aspects of biology, psychology, sociology andspirituality. nurses provide caring services, so nurses are required to be able to meet client needsboth in healthy, sick, and critical conditions. Critical clients in addition to requiring appropriateand fast action, also can not be separated from caring needs and spiritual aspects, because incritical conditions usually clients and families are in a state of resignation and require differentactions compared to clients who are in stable condition. Critical conditions require inner calmand closeness to the God, both for patients and families to be able to go through criticalconditions in a good way. This research is a qualitative research using a phenomenologicalapproach. The purpose of this study is to explore the experience of nurses in providing caringand meeting the spiritual needs of critical patients. Participants in this study were 11 nurses whoworked in the ICU with a minimum of 1 year experience in the ICU. The data were analyzedusing a seven-stage collaizi technique so as to produce four research themes, namely: 1) servingwholeheartedly, 2) improving patient recovery, 3) impact on nurses, 4) nurse expectations forcritical patient care.